HISOR DAVLAT QO‘RIQXONASI UMURTQALI HAYVONLARI AYRIM TURLARINING MAVSUMIY DINAMIKASI - Begaliyev Behruz, Begaliyev Behruz; Xujamqulov Bahrom, Xujamqulov Bahrom (Actual problems and prospects of the study of the fauna, 2024)
Data on the lifestyle, habitat and breeding cycles of the fauna included in the International and the “Red Book”Of The Republic of Uzbekistan were analyzed on the territory of the Hisor State Reserve, and as a result, it was found that there was a change in the dynamics of reproduction in a positive way